2013
DOI: 10.1007/s10048-013-0368-7
|View full text |Cite
|
Sign up to set email alerts
|

Mosaicism for GJB1 mutation causes milder Charcot-Marie-Tooth X1 phenotype in a heterozygous man than in a manifesting heterozygous woman

Abstract: Charcot-Marie-Tooth (CMT) disease is a heterogeneous disorder of the peripheral nervous system that collectively affects approximately 1 in 2,500 individuals, thus making it the most common inherited neurologic disorder. X-linked inheritance may account for 10-20 % of CMT neuropathy. We report a Czech family with a 30-year-old woman affected by CMT since the age of 10 years, originally as an isolated case. Nerve conduction study (NCS) showed demyelinating neuropathy, and DNA testing revealed a novel heterozygo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Mosaicism has been previously reported in other forms of CMT. The clinical manifestation of mosaic status was always present later onset and milder form of the disease, including asymptomatic with normal neurophysiology (Borgulová et al, ; McLaughlin et al, ; Schon et al, ; Spinner & Conlin, ). Hence, the proband's mother was most likely to be explained by the somatic mosaicism.…”
Section: Discussionmentioning
confidence: 99%
“…Mosaicism has been previously reported in other forms of CMT. The clinical manifestation of mosaic status was always present later onset and milder form of the disease, including asymptomatic with normal neurophysiology (Borgulová et al, ; McLaughlin et al, ; Schon et al, ; Spinner & Conlin, ). Hence, the proband's mother was most likely to be explained by the somatic mosaicism.…”
Section: Discussionmentioning
confidence: 99%
“…Mosaicism has been previously reported in other forms of CMT, with a very variable clinical phenotype including asymptomatic with normal neurophysiology studies [12], subclinical disease [13], mild clinical disease [1416] and typical presentations of CMT1A with somatic mosaicism found on genetic testing [1719]. The mutations, level of mosaicism, clinical features and neurophysiology findings from the literature are summarised Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with mild or subclinical CMT due to somatic mosaicism who have been ascertained through an affected child (or grandchild) have been described for CMT1A [16] , CMTX1 [13, 14], and CMT1E [15]. …”
Section: Discussionmentioning
confidence: 99%
“…Mosaicism can be tissue-specific or tissue-limited (Biesecker & Spinner, 2013 ) which is why we performed genetic testing of two different somatic tissues (mesoderm-derived lymphocytes and ectoderm-derived buccal epithelial cells). At the moment, there is only one scientific report on the occurrence of mosaicism in Barth syndrome (Chang et al, 2010 ) but many on the presence of different mosaicism types in other genetic diseases coupled with the X or autosomal chromosomes have been reported (Bakker et al, 1987 ; Puck et al, 1995 ; Forissier et al, 2000 ; Barbosa et al, 2008 ; Chiang et al, 2009 ; Alsina et al, 2013 ; Borgulová et al, 2013 ; Dufendach et al, 2013 ). In this family, it was found that the mutation p.Val28Glu is present in ectodermal as well as in mesodermal cells in the proband's grandmother and male cousin, whereas in samples taken from the proband's mother and aunts the mutation is present only in mesodermal peripheral blood cells or at a low level of mosaicism in ectodermal buccal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%